2001
DOI: 10.1177/107179190100700401
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Hispanic American Involvement in Community Leadership through Volunteerism

Abstract: Executive Summary The purpose of this qualitative study was to identify the Hispanic American involvement in community leadership roles through volunteerism. Twenty Hispanic Americans were interviewed using a 15 item interview schedule. Responses were tape-recorded, translated into English, transcribed, and analyzed using the constant comparative method. Six resulting themes were identified, and corresponding implications discussed: (a) The influence of family and friends on volunteering; (b) the importance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…The participants experienced personal growth and increased self-confidence through their volunteering (Chan, 2011). Some participants reporting becoming braver (Chan, 2011; Daoud et al, 2010), feeling more comfortable in social interaction with foreigners, and improving their interpersonal skills (Safrit & Lopez, 2001). Others reported that volunteering increased their sense of importance, usefulness, and self-worth (Chan, 2011; Daoud et al, 2010; Dudley, 2007; Safrit & Lopez, 2001; H.…”
Section: Second-order Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The participants experienced personal growth and increased self-confidence through their volunteering (Chan, 2011). Some participants reporting becoming braver (Chan, 2011; Daoud et al, 2010), feeling more comfortable in social interaction with foreigners, and improving their interpersonal skills (Safrit & Lopez, 2001). Others reported that volunteering increased their sense of importance, usefulness, and self-worth (Chan, 2011; Daoud et al, 2010; Dudley, 2007; Safrit & Lopez, 2001; H.…”
Section: Second-order Analysismentioning
confidence: 99%
“…Some participants found that volunteering contributed to a sense of belonging in the new country and community (Chan, 2011; Dudley, 2007; Safrit & Lopez, 2001; Wood et al, 2019). In eight studies, the participants reported that volunteering could build strong social relations and friendships (Chan, 2011; Daoud et al, 2010; Dudley, 2007; Handy & Greenspan, 2009; Jensen, 2008; H.…”
Section: Second-order Analysismentioning
confidence: 99%
“…Nelson (2005) discussed that Micro elements of National strategy for Volunteerism show us there are seven basic characteristics of a successful policy which include: a working definition of a volunteer, protection of the rights and obligations of volunteers, budgetary support, publicity and information management, incentives, coordination, and training/technical assistance . Safrit (2001) believes that employees" motivation is major challenge in public sector. Keeping in view the civil service protection, job security and no major accountability, it is difficult for managers to fire, punish or reward employees according to their performance.…”
Section: Volunteerism In Public Sectormentioning
confidence: 99%
“…A second key factor identified in the Safrit and Lopez (2001) study was the influence of the Catholic Church in the recruiting of Hispanic volunteers. According to Swenson (1990), 70% of Hispanics are Catholic, and the local parish, in addition to being a place of worship, serves as a center for social activity, charitable events, celebrations, and promotions of community service.…”
Section: Literature Reviewmentioning
confidence: 99%